Roles of Perilipins in Diseases and Cancers - Zhang, Pengpeng; Meng, Lian; Song, Lingxie; Du, Juan; Du, Shutong; Cui, Wenwen; Liu, Chunxia; Li, Feng (Current Genomics, 2018)
Perilipins, an ancient family of lipid droplet-associated proteins, are embedded in a phospholipid monolayer of intracellular lipid droplets. The core of lipid droplets is composed of neutral fat, which mainly includes triglyceride and cholesterol ester. Perilipins are closely related to the function of lipid droplets, and they mediate lipid metabolism and storage. Therefore, perilipins play an important role in the development of obesity, diabetes, cancer, hepatic diseases, atherosclerosis, and carcinoma, which are caused by abnormal lipid metabolism. Accumulation of lipid droplets is a common phenomenon in tumor cells. Available data on the pathophysiology of perilipins and the relationship of perilipins with endocrine metabolic diseases and cancers are summarized in this mini-review. The research progress on this family offers novel insights into the therapeutic strategies for these diseases.
Keywords: Perilipins